Adipocyte hypertrophy-hyperplasia balance contributes to weight loss after bariatric surgery. (3rd April 2017) - Muir, Lindsey A.; Baker, Nicki A.; Washabaugh, Alexandra R.; Neeley, Christopher K.; Flesher, Carmen G.; DelProposto, Jennifer B.; Geletka, Lynn M.; Ghaferi, Amir A.; Finks, Jonathan F.; Singer, Kanakadurga; Varban, Oliver A.; Lumeng, Carey N.; et al.
ABSTRACT: Predictors of weight loss responses are not well-defined. We hypothesized that adipose tissue phenotypic features related to remodeling would be associated with bariatric surgery weight loss responses. Visceral and subcutaneous adipose tissues collected from patients during bariatric surgery were studied with flow cytometry, immunohistochemistry, and QRTPCR, and results correlated with weight loss outcomes. Age, male sex, and a diagnosis of type 2 diabetes were associated with less weight loss. Adipocyte size was increased and preadipocyte frequency was decreased in visceral adipose tissue from diabetic subjects. Decreased adipose tissue preadipocyte frequency was associated with less weight loss in women but not men. These data suggest that phenotypic features of adipose tissue remodeling may predict responses to weight loss interventions.